2022
DOI: 10.1007/s10980-022-01419-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dynamic of nestedness in bird assemblages inhabiting fragmented landscapes

Abstract: Context Nestedness is a common pattern of species assemblages in fragmented landscapes. The spatial pattern and ecological drivers of nested communities have been widely explored, but few studies investigated their long-term variability. Objectives To investigate the variability of nestedness and species-specific fragment occupancy of forest birds in a fragmented landscape affected by environmental changes over 16 years. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Thus, the bias brought by inventory completeness is actually weak (Colwell & Elsensohn, 2014). We are also aware that the imperfect detection of rare species may bias estimates of species richness (Dondina et al, 2022; Wang et al, 2015). Indeed, some species showed lower abundance on islands (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the bias brought by inventory completeness is actually weak (Colwell & Elsensohn, 2014). We are also aware that the imperfect detection of rare species may bias estimates of species richness (Dondina et al, 2022; Wang et al, 2015). Indeed, some species showed lower abundance on islands (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A study in forest fragments further suggested that the ordered loss of traits from specific habitats induced the functional nestedness of frog communities (Almeida‐Gomes et al, 2019). However, most of these views were based on short‐term responses of species from habitat islands, and less is known about the functional and phylogenetic adaptation of amphibians to long‐term isolated insular systems (but see Dondina et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Dispersal ratio, a surrogate of species mobility and dispersal ability [89,90], showed that species with higher dispersal ability would not tend to expand the niche, but findings were inconclusive in respect to unfilling. We also have to consider that the dispersal ratio could be an inappropriate indicator of the dispersal ability [64,126], as well as that habitat configuration and landscape connectivity significantly affect the dispersal process [127], leading to idiosyncratic responses between species. Regarding the degree of species specialization (Dim2 of PCA), niche metrics were not linked with it, although a weak signal showed that specialist birds tend to retain their niche more than generalist ones.…”
Section: Relationship Between Nyche Temporal Changes Population Trend...mentioning
confidence: 99%
“…Our study differs from previous nestedness studies in several ways. First, although nestedness has been documented for a variety of taxa ( Wright et al 1998 ; Watling and Donnelly 2006 ; Dondina et al 2022 ), it is rarely examined in lizard assemblages from oceanic archipelago systems ( Perry et al 1998 ). Our study on lizards thus fills in a significant gap and contributes to the ecological generality of nestedness across a wide range of taxa.…”
Section: Discussionmentioning
confidence: 99%